Self-Defense, Forfeiture, and Necessity. (2nd September 2019) - Alm, David
Abstract: The thesis of this paper is that it is possible to explain why a culpable aggressor forfeits his right not to suffer the harm necessary to prevent his aggression if a killer forfeits his right to life. I argue that this strategy accounts also for the necessity restriction on self-defense. I respond to several objections, including the worry that it makes no sense to attempt a derivation of the relatively uncontroversial (aggressor's forfeiture) from the highly controversial (killer's forfeiture).